2016
DOI: 10.3906/sag-1504-100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Borrelia burgdorferi sensu lato seroprevalencein the province of Bolu, Turkey*

Abstract: disease is a multisystemic disease caused by Borrelia species, and it is transmitted to humans by ticks of the species Ixodes. There are three genotypes of the Lyme disease agent: Borrelia burgdorferi sensu stricto, Borrelia garinii, and Borrelia afzelii. They are grouped together under the name B. burgdorferi sensu lato (1). The causative agent of Lyme disease, B. burgdorferi, was isolated in 1982 (2). Lyme disease is evident in three stages. The first stage includes erythema migrans (EM) and needs no serolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
(10 reference statements)
1
11
0
2
Order By: Relevance
“…When the seroprevalence rates were examined for North American, European, and Asian countries where LD is prevalent, the prevalence of B. burgdorferi IgG varied between 4% and 13% (29)(30)(31). In Turkey, the positivity of B. burgdorferi IgG was found to be 0.9% in the provinces of Van and Manisa, 4.6% in Bolu, and 6% in Düzce (by the present study) (32)(33)(34). The difference between the regions could be attributed to geographical location, climatic conditions, and species of ticks living in the region.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…When the seroprevalence rates were examined for North American, European, and Asian countries where LD is prevalent, the prevalence of B. burgdorferi IgG varied between 4% and 13% (29)(30)(31). In Turkey, the positivity of B. burgdorferi IgG was found to be 0.9% in the provinces of Van and Manisa, 4.6% in Bolu, and 6% in Düzce (by the present study) (32)(33)(34). The difference between the regions could be attributed to geographical location, climatic conditions, and species of ticks living in the region.…”
Section: Discussionmentioning
confidence: 48%
“…Studies on the seroprevalence of B. burgdorferi have reported that the seroprevalence of LD is low in groups with high socioeconomic and educational levels (28,35). Bucak et al (33) found that the prevalence was higher in the illiterate population than in the literate population. In the current study, it was observed that B. burgdorferi IgG positivity decreased as the level of education increased.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, 985 inpatient admissions for LD and 44,445 outpatient LD diagnoses between the years of 2005 and 2010 were reported with an estimated annual incidence as 106.6 cases per 100,000 persons. 44 Seroprevelance studies on LD show that Borrelia burgdorferi seropositivity is in the range of 0.9-14.5% in different cities of Turkey, [45][46][47][48][49][50] whereas these rates are in the range of 2.6-5.4% in different subgroups and different countries of Europe. 51,52 Weather conditions or regional distribution of specific tick vectors may explain these differences.…”
Section: Discussionmentioning
confidence: 99%
“…[5] tarafından 2010 yılında bildirilmiştir. Türkiye'den bazı seroepidemiyolojik çalışmalar Tablo 1'de sunulmuştur [6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . Ülkemizde hastalık bildirimi zorunlu hastalıklar kategorisine alınarak "Klinik Bakteriyoloji Tanı Standartları Çalışma Grubu" tarafından referans laboratuvar özellikleri standardize edilmiş ve Türkiye Halk Sağlığı Kurumu tarafından düzenlenmiştir [31] .…”
Section: Epidemiyolojiunclassified
“…Tablo 1. Türkiye'de insan, kene, fare ve atlarda yapılan bazı seroepidemiyolojik çalışmalar [6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Yazar/referans Çalışma türü Coğrafi bölge…”
Section: Epidemiyolojiunclassified